The association between serum adiponectin and 3-month outcome after ischemic stroke - Zengliang Wang; Bo Li; Yongxin Wang; Aisha Maimaitili; Hu Qin; Geng Dangmurenjiafu; Shuo Wang (Cardiovascular Diabetology, 2019)
Abstract Background Although adiponectin is a major adipocytokine that affects the pathogenesis of various cardiovascular diseases, its clinical significance in stroke remains controversial. The purpose of this study was to assess the impact of serum adiponectin levels on functional prognosis in patients with ischemic stroke. Methods This was a prospective, observational cohort study. Consecutive first-ever ischemic stroke patients without any pre-morbid handicap admitted to our hospital were identified from December 2017 to December 2018. Serum concentration of adiponectin was routinely measured within the first 24 h after admission by a commercially available sandwich ELISA. Associations between adiponectin and either clinical severity at admission, poor outcomes or mortality at 3-month after admission were analyzed using logistic regression to obtain odds ratios (OR) and 95% confidence intervals (CI). Results The serum level of adiponectin was obtained in 227 patients with a median value of 7.0 μg/ml, which was significantly higher (P < 0.001) than in those heathy control. Adiponectin levels were associated with moderate-to-high stroke, and risk increased by 12% (OR = 1.12; 95% CI 1.03–1.25; P = 0.002). Patients with a poor outcome and nonsurvivors had significantly increased adiponectin levels on admission (P < 0.001, all). In multivariate logistic regression analysis, adiponectin was an independent predictor of functional outcome and mortality, and risk increased by 24% (OR = 1.24, 95% CI 1.13–1.37; P < 0.001) and 31% (1.31 [1.18–1.46], P < 0.001), respectively. Kaplan–Meier analysis suggested that the patients with high serum adiponectin levels had a higher risk of death than those patients with low levels (log-rank test P < 0.001). Conclusions Our results show that high adiponectin is associated with stroke severity and support the hypothesis that adiponectin can be serve as a biomarker of poor outcome after stroke, independent of baseline variables. Trial registration ChiCTR-OPC-17013501. Retrospectively Registered 21 September 2017